The Systematization of Psychophysical Developmental Disorders of Early Age Children - Valitova, Irina (Psychological Prospects Journal, 2018)
The regularities of disturbances in the psychophysical development of the child at an early age are investigated in special psychology insufficiently in comparison with later ages. The existing classifications of types of developmental disorders are not created for the early age, which complicates both the scientific research and the practical work of psychologists in the system of early intervention. Early age – the period from one year to three years – is traditionally regarded as a sensitive period for the child development, it characterized by a high tempo of psychophysical development; a child at this age is easily exposed to the harmful effects of biological and psychological factors. However, a holistic picture of the regularities of violations of child development at an early age is absent.The article presents classifications of developmental disorders which have been worked out in child neurology, child psychiatry, special psychology and correctional pedagogy. Their limitations are shown in relation to the characteristics of developmental disorders in young children: important types of disorders are not included, it is inapplicable to very small children. There is only one classification DC 0-3, which presents the types of developmental disorders in children from very birth to three years, but it considers emotional and behavioral disorders in children and is not included, in particular, speech and cognitive development disorders, motor function disorders.A model of disturbances in the psychophysical development of early age children is proposed in the article, in which available scientific data are systematized: the model is based at the concept of primary and secondary defects in the structure of psychophysical development. The leading sphere, which is violated in the first place in the structure of the child’s psychophysical development, has been chosen as a criterion for classifying the types of developmental disorders.
Keywords: early age, children of early age, disorders of psychophysical development, systematization of developmental disorders, primary and secondary disorders.